Measurement error associated with performance testing in well-trained cyclists: Application to the precision of monitoring changes in training status - Lamberts, S.; Swart, J.; Woolrich, R. W.; Noakes, T. D.; Lambert, M. I. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Small changes in performance, as low as 1%, are regarded as meaningful in well-trained cyclists (1,2). Being able to detect these relatively small changes is necessary to accurately prescribe training and optimize performance. The typical error of measurement (TEM) in common performance cycle tests is about 2-3% (3). It is not known whether this TEM is lower in well-trained cyclists and therefore whether small changes in performance parameters are detectable. Methods: After familiarisation, 17 well-trained cyclists were recruited for the study. They were required to complete three Peak Power Output (PPO) tests (including VO2max) and three 40km time trials (40km TT). All tests were performed after a standardized warm-up at the same relative intensity (LSCT) and under a strict testing-protocol. Results: Fifteen cyclists successfully competed the study and the data of 2 cyclists had to be excluded because of violated the protocol by using a potential performance enhancing drugs (4) and not completing the study. The TEM within the PPO-test was 2.2% for VO2max and 0.9% for PPO, while TEM for the 40km TT was 0.9%. Conclusion: This study shows that the measurement of PPO and 40km TT time, after a standardized warm-up (LSCT), has sufficient precision in well-trained cyclists to detect small meaningful changes. In contrast the TEM associated with VO2max was too high to be of practical value for tracking performance, and should therefore be interpreted with caution when monitoring cyclists. The findings of this study contribute to a more accurate determination of what should be regarded as a meaningful change in already well-trained cyclists. This will allow a more accurate assessment of the effectiveness of training programs, and possibly narrows the discrepancy between what trainers, coaches and elite cyclists belief to be effective and what scientists can proof to support this conviction.